Numerical analysis of momentum transfer processes in a mechanically agitated air – biophase – liquid system - Musiał Monika; Cudak Magdalena; Karcz Joanna (Chemical and Process Engineering)
The results of numerical computations concerning momentum transfer processes in an air – biophase – liquid system agitated in a bioreactor equipped with baffles and a Smith turbine (CD 6 impeller) are presented in this paper. The effect of sucrose concentration on the distributions of the velocity of the continuous phase, gas hold-up and the size of gas bubbles in the system was analysed. Simulation results were presented in the form of the contours of the analysed magnitudes. The effect of sucrose concentration on the averaged values (i.e. determined on the basis of local values) of gas hold-up and gas bubbles size was evaluated. The results of the numerical computations of gas hold-up were compared with our own experimental data.